2012
DOI: 10.1107/s0907444912001862
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure-induced water penetration into 3-isopropylmalate dehydrogenase

Abstract: Hydrostatic pressure induces structural changes in proteins, including denaturation, the mechanism of which has been attributed to water penetration into the protein interior. In this study, structures of 3-isopropylmalate dehydrogenase (IPMDH) from Shewanella oneidensis MR-1 were determined at about 2 Å resolution under pressures ranging from 0.1 to 650 MPa using a diamond anvil cell (DAC). Although most of the protein cavities are monotonically compressed as the pressure increases, the volume of one particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Collins et al (2005) reported water filling ISSN 1399-0047 of the nonpolar interior cavity of L99A mutant T4 lysozyme. As the initial steps of pressure denaturation, Nagae et al (2012) also observed water penetration into the hydrophobic cavity at the dimer interface and a cleft on the surface of IPMDH. To further study high-pressure effects in proteins, including pressure-induced changes in hydration structure, we used HPPX to study the well known tetragonal crystal of HEWL.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Collins et al (2005) reported water filling ISSN 1399-0047 of the nonpolar interior cavity of L99A mutant T4 lysozyme. As the initial steps of pressure denaturation, Nagae et al (2012) also observed water penetration into the hydrophobic cavity at the dimer interface and a cleft on the surface of IPMDH. To further study high-pressure effects in proteins, including pressure-induced changes in hydration structure, we used HPPX to study the well known tetragonal crystal of HEWL.…”
Section: Introductionmentioning
confidence: 92%
“…To collect high-completeness data sets at each pressure, we inserted two or three crystals into the DAC at different orientations. To prevent the crystals from moving in the DAC sample chamber, the crystals were fixed with tied fibres from cigarette filters (Nagae et al, 2012). The pressure in the DAC was gradually increased to the target pressure in about 10-15 min, and the DAC was left for about 10 min.…”
Section: High-pressure Protein Crystallography Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in pressure induced protein unfolding, water may play a role in oligomer dissociation by pressure due to a "destruction of voids" mechanism. For instance, crystallographic studies at different pressures of the dimeric (∼ 340 residues/monomer) enzyme 3-isopropylmalate dehydrogenase (IPMDH), a pressure sensitive enzyme in the biosynthesis pathway of leucine, from the mesophilic Shewanella oneidensis [50] shows water inside a cavity at the interface of the two monomers between 4.1 to 5.8 kbar while no water is present at 1 bar ( figure 3). This cavity may be a pressure sensitive point for dimer dissociation.…”
Section: -4mentioning
confidence: 99%
“…The results from these simulations also indicate that µs simulations are needed to evaluate the changes in structural properties at different pressures since very low frequency motions are apparent. High-pressure crystallographic studies of monomeric and dimeric proteins have been used to estimate the compressibility to be between 4 to 6 Mbar −1 [50,53,54], and internal cavities within the monomers of IPMDH have been shown to be compressed monotonously up to 6.5 kbar [50], indicating that the cavities allow the protein to be more compressible.…”
Section: Limits Of Growth: Compaction and Conformational Changes Of Pmentioning
confidence: 99%